Effectiveness of biologic therapies on psoriasis vulgaris - Christabela Tansuri, Verika; Wijayadi, Linda Julianti (Institute of Computer Science (IOCS), 2024)
Psoriasis is a chronic proliferative inflammatory condition mediated by the immune system that is characterized by erythematous plaques covered by silvery scales. Psoriasis vulgaris is mediated by T lymphocytes, wherein the activation of innate immune cells and pathogenic T cells leads to inflammation of the skin and excessive growth of keratinocytes. The pathogenesis of psoriasis vulgaris has significantly enhanced comprehension of cutaneous immunology, facilitating an introduction to highly effective therapies. Biologic therapy binds to a specific cytokine such as TNF-α, IL-12, IL-17, or IL-23, unlike non-biologic therapy primarily focuses on resolving clinical manifestation without targeting the underlying causes. A literature review was performed to present the effectiveness of biologic therapies as a part of psoriasis vulgaris management.